Konsep Penataan Permukiman Berbasis Wisata Budaya di Kelurahan Melai, Kecamatan Murhum Kota Baubau - Wirman Ramadhan; Yusni Mustari; Wiwik Wahidah Osman (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2013)
Melai village is located in the district of Buton Palace Fort is an ex-central of Buton Sultanate. The region has significance in the development of tourism in Baubau City. In this area there are a wide variety of cultural attractions such as traditional buildings, historic sites and traditions of Buton Sultanate local community. The characteristic of cultural tourism is different from other regions. The characteristic become a major attractor of tourists to visit this area. However, the land use have not been supported by a good management as settlements pattern, utilization and management of potential heritage tourism of the Sultanate of Buton and support facilities in the district. This study aims to develop a concept of structuring the settlements based on cultural tourism in the Melai. The analysis used is a comparative analysis, zoning analysis, the analysis of spatial and SWOT analysis to determine regional structuring strategy. The analysis produced some structuring strategies can be optimized so that the potential of the region. The strategy consists of structuring the arrangement of residential areas by way of strengthening the regulation and planning of basic infrastructure and facilities to support tourism activities in the region.